Genetic variation in scaly hair-fin anchovy Setipinna tenuifilis (Engraulididae) based on the mitochondrial DNA control region. (June 2014) - Xu, Shengyong; Song, Na; Lu, Zhichuang; Wang, Jun; Cai, Shanshan; Gao, Tianxiang
Abstract Scaly hair-fin anchovy (Setipinna tenuifilis) is a small, pelagic and economical species and widely distributed in Chinese coastal water. However, resources of S. tenuifilis have been reduced due to overfishing. For better fishery management, it is necessary to understand the pattern of S. tenuifilis's biogeography. Genetic analyses were taken place to detect their population genetic variation. A total of 153 individuals from 7 locations (Dongying, Yantai, Qingdao, Nantong, Wenzhou, Xiamen and Beibu Bay) were sequenced at the 5′ end of mtDNA control region. A 39-bp tandem repeated sequence was found at the 5′ end of the segment and a polymorphism of tandem repeated sequence was detected among 7 populations. Both mismatch distribution analysis and neutrality tests showed S. tenuifilis had experienced a recent population expansion. The topology of neighbor-joining tree and Bayesian evolutionary tree showed no significant genealogical branches or clusters of samples corresponding to sampling locality. Hierarchical analysis of molecular variance and conventional pairwise population Fst value at group hierarchical level implied that there might have genetic divergence between southern group (population WZ, XM and BB) and northern group (population DY, YT, QD and NT). We concluded that there might have three different fishery management groups of S. tenuifilis and the late Pleistocene glacial event might have a crucial effect on present-day demography of S. tenuifilis in this region.